EKSPERIMENTASI MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI), PROBLEM BASED LEARNING (PBL) DAN PEMBELAJARAN KLASIKAL DENGAN PENDEKATAN SAINTIFIK PADA MATERI BENTUK ALJABAR DITINJAU DARI AKTIVITAS BELAJAR SISWA - Suprapto, Suprapto; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Journal of Mathematics and Mathematics Education, 2016)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from student’s leraning activity. The learning models compared were TAI with scientific approach, PBL with scientific approach, and classical with scientific approach.This experiment was quasi-experimental. It uses 3 x 3 factorial planning. The population was the entire 8th grade students of State Junior high School in Grobogan regency in the academic year 2014/2015. The sampling technique used was stratified cluster random sampling. The sample consisted of students of SMP N 2 Tegowanu, SMP N 3 Godong and SMP N 5 Purwodadi. Data collection instruments used were learning achievement test and student learning activity questionnaire. Hypothesis examination used was variance analysis (anava) with unequal cell.Conclusions acquired from this thesis are as follows: 1) PBL using scientific approach gives better mathematics learning achievement compared to TAI and classical Learning, TAI using scientific approach gives better mathematics learning achievement compared to classical learning. 2) student’s mathematics achievement with high learning activity is better than those with intermediate and poor learning activity, intermediate learning activity is better than those with poor learning activity. 3) on TAI using scientific approach, student’s mathematics achievement with high learning activity is as good as those with intermediate learning activity, high learning activity is better than those with poor learning activity, and intermediate learning activity is good as those with poor learning activity. Students which is given PBL using scientific approach, students with high learning activity have mathematics learning achievement as good as those with intermediate learning activity, high learning activity is better than those with poor learning activity, and intermediate learning activity is good as those with poor learning activity. 4) for students with high learning activity, PBL gives learning achievement as good as TAI, PBL gives learning achievement better than classical learning, and TAI gives learning achievement better than classical learning. For students with intermediate learning activity; TAI, PBL and classical learning gives the same good result. For students with poor learning activity; TAI, PBL and classical learning gives the same good result on student’s learning achievement. And student’s learning achievement on algebra which is given PBL is as good as those which is given classical learning.Keywords: TAI using scientific approach, PBL using scientific approach, classical learning, learning activity, learning achievement